The adverbial and prepositional usage of relational preposition-forming adverbs such as zraven, blizu, skozi, čez and okoli - Žele, Andreja (Slavia Centralis, 2021)
This article addresses the contemporary use of relational adverbs in Slovenian from the point of view of synchronic linguistics. The term 'relational adverbs' refers to adverbs of spatial relations whose syntactic-semantic roles are closest to those of prepositions. For this reason, they can be converted into full adjuncts or into prepositions. This ability to function as two different parts of speech has been normalised to such a degree with relational adverbs that lexicographers typically treat them as two separate lemmata: one classified as an adverb and the other classified as a preposition.
Keywords: adverbs; adjectives; semantic feature; conversion; syntactic roles